Discovery of HLA‐B*51:209, a novel HLA‐B*51 variant, in a Taiwanese individual. (17th November 2016) - Yang, K. L.; Lin, P. Y.
Abstract : One nucleotide substitution at residue 85 of HLA‐B*51:01:01:01 results in a novel allele, HLA‐B*51:209 .